Isolasi dan Pengklonan Fragmen cDNA Gen Penyandi H+-ATPase Membran Plasma dari Melastoma malabathricum L. - , Muzuni; Didy Sopandie; Utut Widyastuti Suharsono; , Suharsono (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
Melastoma malabathricum L. grows well in acid soil with high level of soluble aluminum. One of the important proteins in the detoxifying acid and aluminum stress is a plasma membrane H+ -ATPase protein encoded by PMA gene. The objective of this research was to isolate and clone the cDNA fragment of MmPMA encoding plasma membrane H+ -ATPase from M. malabathricum L. By reverse transcription, total cDNA had been synthesized from the total RNA as template. The fragment of MmPMA cDNA had been successfully isolated by PCR by using total cDNA as template and PMA primer designed from conserved region for corresponding gene. This fragment had been successfully inserted into pGEM-T Easy and the recombinant plasmid was successfully introduced into E. coli DH5